Conservation Agriculture Boosts Soil Health, Wheat Yield, and Nitrogen Use Efficiency After Two Decades of Practice in Semi-Arid Tunisia - M'hamed, Hatem Cheikh; Ferchichi, Nouha; Toukebri, Wael; Barbouchi, Meriem; Moujahed, Nawel; Rezgui, Mohsen; Bahri, Haithem; Sassi, Khaled; Frija, Aymen; Annabi, Mohamed (MDPI, 2024)
Conservation agriculture (CA) has been proposed as a viable strategy to enhance soil health and the resilience of farms to climate change, and to support the sustainability of agricultural production systems. While CA is a well-established approach, research results are lacking regarding its long-term impact on nitrogen (N) dynamics in the soil–plant system. In this study, a 20-year experiment was used to investigate the long-term effects of no-tillage in CA on soil organic carbon (SOC) and nitrogen (N) mineralization, plant N uptake, grain yields, and the grain quality of durum wheat. A CA system based on no-tillage (NT) was evaluated and compared with conventional tillage (CT) used for wheat/legumes biennial crop rotation. Results showed that soil samples from CA plots experienced significantly more N mineralization than those under CT, which was attributed to increased SOC and N. Topsoil sampled from the CA plots 20 years after the implementation of the experiment had 43% more absolute potentially mineralizable N (N0) than the CT plots, with no significant differences observed in deeper soil layers (15–30 cm and 30–45 cm). The absolute potentially mineralizable carbon (C0) in soils from the CA system was 49% and 35% higher than in soils from the CT system, at soil depths of 0–15 and 15–30 cm, respectively. Furthermore, CA resulted in higher amounts of remobilized N and higher rates of N uptake during the critical growth stages of durum wheat. The amount of N remobilized during the kernel-filling phase under CA was 59% higher than under CT. Total N uptake in wheat plants was 45% greater under CA compared to CT. The most significant differences in N uptake between the CA and CT systems were observed during two critical growth stages: late tillering to heading (1.7 times higher in CA than CT) and heading to anthesis (1.5 times higher in CA than CT). The most significant differences for N uptake were shown during the late tillering to heading stage and the heading to anthesis stage. The amount of N remobilized during the kernel filling phase under CA was 59% higher than CT. CA adoption resulted in 21% and 35% higher grain and straw yields, respectively, compared to CT. The grain and straw N yields were 21% and 51% higher, respectively, under CA than CT. Moreover, the CA system exhibited higher partial factor productivity of nitrogen fertilizer (PFP N) for both grain and straw yields. Thousand kernel weight (TKW) and hectoliter weight were also significantly higher under CA than CT. The grain protein content, wet gluten content, vitreousness, and falling number were similar between the CA and CT systems. These results highlight the benefits of long-term CA adoption to increase soil N mineralization, providing a substantial base for N uptake during the critical growth stages of durum wheat, thus leading to increased crop yield. The findings underscore the potential of CA systems in promoting sustainable agriculture and mitigating the impacts of soil degradation.